Safety and Efficacy of Buparlisib (BKM120) in Patients with PI3K Pathway-Activated Non-Small Cell Lung Cancer: Results from the Phase II BASALT-1 Study. Issue 9 (September 2015) - Vansteenkiste, Johan F.; Canon, Jean-Luc; Braud, Filippo De; Grossi, Francesco; De Pas, Tommaso; Gray, Jhanelle E.; Su, Wu-Chou; Felip, Enriqueta; Yoshioka, Hiroshige; Gridelli, Cesare; Dy, Grace K.; Thongprasert, Sumitra; et al.
Abstract : Introduction: The phosphatidylinositol 3-kinase (PI3K) pathway promotes tumor growth and treatment resistance in non-small cell lung cancer (NSCLC). The aim of the open-label, two-stage, Phase II study BASALT-1 (NCT01820325) was to investigate the pan-PI3K inhibitor buparlisib (BKM120) in patients with PI3K pathway-activated, relapsed NSCLC. Methods: After prescreening for PI3K pathway activation, patients with PI3K pathway-activated, metastatic, squamous or nonsquamous NSCLC, who had relapsed after prior systemic antineoplastic therapy, were enrolled. In Stage 1, patients received single-agent buparlisib (100 mg/day). A futility analysis was performed independently in each histology group, based on the 12-week progression-free survival rate for the first 30 patients treated in each group being less than 50%. Exploratory biomarker analyses were performed in archival tissue samples and circulating tumor DNA (ctDNA). Results: Of 1242 prescreened patients, 13.5% exhibited PI3K pathway activation. As of June 5, 2014, 63 patients (30 squamous and 33 nonsquamous) were treated in Stage 1. The 12-week progression-free survival rates were 23.3% (95% confidence interval: 9.9–42.3) and 20.0% (95% confidence interval: 7.7–38.6) in the squamous and nonsquamous groups, respectively. Stage 2 was therefore not initiated in either group. PI3K pathway mutations in ctDNA were more concordant with metastatic tissue than with primary biopsies. Conclusions: Despite preselecting patients for targeted treatment, BASALT-1 did not meet its primary objective during Stage 1. PI3K pathway activation can be detected using ctDNA, but may not be the main oncogenic driver in NSCLC. Combinations of PI3K inhibitors with other agents may demonstrate greater efficacy than monotherapy.